Políticas públicas de saúde da criança e do adolescente: uma reflexão ética na visão do profissional de enfermagem - Pinheiro, Lívia Mara Gomes (2013)
This study aims at providing the comprehension which a nursing professional should have of the ethical issues involved in the actions of the work of his/her profession in the context of health care and the complex network of multi-professional relations, analyzing the positive and negative aspects of these actions, having as a reference the values which give rise to them and which are called, in their broad sense, ethics. Besides this, it aims at reflecting on the action of this professional as it relates to the public policies attending the health of the child and of the adolescent, this issue being considered vital with regard to the assumptions related to Professional Ethics. The methodology used was bibliographic research, the method of which has as its goal to understand the existing theoretical information about the problem-situation, that is, the ethical-professional issues of nursing with an emphasis on the public policies attending the child and the adolescent and their inter-relations.